PERAN BIMBINGAN KONSELING ISLAM DALAM MENINGKATKAN EFEKTIVITAS PENYULUHAN KESEHATAN MASYARAKAT - Damar Retno Dhyanti; Aep Kusnawan; Sugandi Miharja (Universitas Nias Raya, 2025)
This study aims to analyze the role of Islamic guidance and counseling in enhancing the effectiveness of public health outreach. The research employed a library research method complemented by in-depth interviews with health educators at Giri Mande Community Health Center. The findings indicate that Islamic guidance and counseling can integrate psychological, educational, and spiritual aspects into health outreach activities, creating a more holistic and comprehensive approach. This approach positively impacts individuals’ understanding of their health conditions while fostering healthy lifestyle behaviors and discipline in maintaining good living habits. The integration of Islamic values such as tawakkul (trust and reliance on Allah) and dzikir (remembrance of Allah) also strengthens participants’ mental and spiritual aspects, enabling them to face health challenges with mental readiness and spiritual calm. Moreover, Islamic counseling contributes to comprehensive health education, including mental health, reproductive health, and disease prevention, through a more personal and contextualized approach. Therefore, Islamic guidance and counseling not only serve as an educational medium but also as a tool for empowering individuals to achieve physical, mental, and spiritual well-being. This study emphasizes that integrating spiritual values into health outreach is an effective strategy for promoting public health comprehensively